2019
DOI: 10.1108/bij-09-2017-0245
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and analysis of barriers affecting the implementation of lean green agile manufacturing system (LGAMS)

Abstract: Purpose Many types of research have already investigated the lean, green or agile manufacturing systems in a discrete manner or as combinations of two of them. In today’s competitive scenario, if industry wants to perpetuate its name in the market, then it has to supervene proper thinking and smart approach. Therefore, the combination of lean, green and agile manufacturing systems can provide better and beneficial results. The purpose of this paper is to discern the barriers to the combined lean green agile ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 77 publications
3
59
0
3
Order By: Relevance
“…When specifically used for Lean Six Sigma, these information technologies of Industry 4.0 make the entire implementation process Simple, Speedy, and Smart (Park et al 2020). Many barriers for Lean Six Sigma implementation, e.g., improper communication, inadequate data collection; highlighted by Sindhwani et al (2019) can be overcome using Quality 4.0 framework. However, it requires meticulous planning and painstaking execution.…”
Section: Quality 40mentioning
confidence: 99%
See 3 more Smart Citations
“…When specifically used for Lean Six Sigma, these information technologies of Industry 4.0 make the entire implementation process Simple, Speedy, and Smart (Park et al 2020). Many barriers for Lean Six Sigma implementation, e.g., improper communication, inadequate data collection; highlighted by Sindhwani et al (2019) can be overcome using Quality 4.0 framework. However, it requires meticulous planning and painstaking execution.…”
Section: Quality 40mentioning
confidence: 99%
“…Jha et al (2019) established CSF for LSS in Indian manufacturing companies. Sindhwani et al (2019) reported CSF when LSS is implemented with other strategies, e.g., Agile and Green. CSF for LSS use in a nonspecific business unit are also available (Laosirihongthong et al 2006;Sreedharan et al 2018).…”
Section: Critical Success Factors (Csf) For Lean Six Sigma (Lss) Using Quality 40mentioning
confidence: 99%
See 2 more Smart Citations
“…Chi tiết thể hiện qua Bảng 2 như sau: Như vậy chúng tôi thu thập được bốn bài báo thỏa mãn yêu cầu. Chúng tôi tiến hành đọc nội dung những bài viết này Sindhwani et al (2019). liệt kê 13 rào cản khi triển khai đồng thời 3 chiến lược: Lean-Green-Agile (Bảng 2), do đó có thể sẽ có một số rào cản mà chúng ta sẽ không đề cập khi chúng ta đang thảo luận về Lean.…”
unclassified